The power of boycotts: voices of protest and solidarity / Daing Maruak Sadek and Azyyati Anuar - Sadek, Daing Maruak; Anuar, Azyyati (Universiti Teknologi MARA, Kedah, 2024)
A boycott is a powerful form of protest wherein individuals or groups conscientiously abstain from purchasing or utilizing the products or services associated with a specific company, nation, or individual.